The dark perimetric stimulus. Issue 5 (May 1992) - Mutlukan, E; Damato, B E
Abstract : We determined the disappearance eccentricities of dark and bright stimuli of equal size in the inferonasal central visual field using the oculokinetic perimetry technique at different levels of surrounding illumination. The results suggest that a dark stimulus on a bright background has a smaller 'isoptre' than an equally bright stimulus on a dark background, and that variation of ambient illumination and consequent alteration of background luminance have less effect on the visibility of a dark stimulus than a bright one.